HUBUNGAN INTENSITAS MEMBACA ALQURAN DAN PEMBIASAAN SHOLAT DHUHA TERHADAP KEDISIPLINAN BERIBADAH SISWA MI ISLAMIYAH MUHAMMADIYAH WALIKUKUN - Yuliana Ayu Febriarianti; Zulfa Istinwaro Holik; Bunga Desti Pratiwi (JOURNAL J-MPI : JURNAL MANAJEMEN PENDIDIKAN, PENELITIAN DAN KAJIAN KEISLAMAN, 2026)
This study aims to analyze the influence of the intensity of reading the Al-Qur'an and the habituation of dhuha prayer on the religious discipline of students at MI Islamiyah Muhammadiyah Walikukun. Using a quantitative correlation approach, data were collected through questionnaires from a sample of 35 students in grade IV A, selected using a random sampling technique. Data analysis was performed using multiple linear regression. The results showed that simultaneously, the intensity of reading the Al-Qur'an and the habituation of dhuha prayer have a significant relationship with religious discipline, with an F-value of 27.494 and a significance level of 0.000. Partially, the dhuha prayer habituation variable exerted a dominant and significant influence (p = 0.002), while the intensity of reading the Al-Qur'an did not show a statistically significant effect (p = 0.078). These findings indicate that routine sunnah worship practices, such as dhuha prayer, are more effective key factors in increasing students' religious consistency at school. This study recommends strengthening daily worship habituation programs as a strategy for Islamic character development.